A Literature Study on Investment Pattern and Choices of Salaried People - Hooda, Jayant; Kanwa, Anil; Gupta , Sonal (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
The level of investment needs to increase for achieving a high growth and development level in the economy. The initial planning stage considers investment as a vital tool for increasing national income and economic growth. This financial global place shows a balanced but weird influence of the favoured investment of individuals, their knowledge regarding the needs of investment, return estimation from investment etc.  The prediction of the development of this global business is difficult without comprehending the opposite behaviour of investment of significant constituents of society. A lot of choices are offered for investment purposes and the individual must choose the appropriate ones for the portfolio. The one who deals with the planning phase must have information of all the investment alternatives and how the investor selects the alternative for achieving the overall goals and aims. The investor chooses the best option after the evaluation of key features linked with the investment like the stability of income, liquidity, risk, return, time, transferability and payback of principal amount. This study focuses on the pattern and choices of Investors regrading investment options and the factors influencing the behaviour of investor while selecting the option. Data is gathered from secondary sources such as research papers, research articles, journals, thesis and websites.  The results of the study are based on investment patterns and choice of investor regarding different alternatives on the basis of existing reviews